2014
DOI: 10.1055/s-0034-1390013
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Magnetic Resonance Imaging of the Skull Base

Abstract: Introduction Over the past 20 years, magnetic resonance imaging (MRI) has advanced due to new techniques involving increased magnetic field strength and developments in coils and pulse sequences. These advances allow increased opportunity to delineate the complex skull base anatomy and may guide the diagnosis and treatment of the myriad of pathologies that can affect the skull base. Objectives The objective of this article is to provide a brief background of the development of MRI and illustrate advances in sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…3D FT T1W sequences with 0.6–1-mm-thin slices (VIBE-Volumetric Interpolated Examination) after intravenous contrast administration are additionally used by some investigators including ourselves. These volumetric data sets allow multiplanar reconstructions in any given plane and thereby facilitate the evaluation of subtle abnormalities [ 8 ].…”
Section: Imaging Anatomy Contents and Major Communications Of The Pmentioning
confidence: 99%
See 1 more Smart Citation
“…3D FT T1W sequences with 0.6–1-mm-thin slices (VIBE-Volumetric Interpolated Examination) after intravenous contrast administration are additionally used by some investigators including ourselves. These volumetric data sets allow multiplanar reconstructions in any given plane and thereby facilitate the evaluation of subtle abnormalities [ 8 ].…”
Section: Imaging Anatomy Contents and Major Communications Of The Pmentioning
confidence: 99%
“…Osseous abnormalities are best seen on CT whilst replacement of fat is best seen on T1W MR images. Contrast-enhanced T1W MR images, especially with fat-saturation, can elegantly demonstrate PNS within the PPF [ 5 8 ].…”
Section: Key Ct and Mr Imaging Appearances In Ppf Pathologymentioning
confidence: 99%
“…4,8,11 The evolution of imaging studies allowed better staging and delineation of the tumor extension to involved structures. 12 In the current study, the multivariate analysis found that intracranial tumor extension was a predictor for complication development. We routinely use magnetic resonance imaging, computed tomography (CT), and positron emission tomography-CT studies to assess tumor extension and to select the preferred reconstruction method.…”
Section: Averting Complicationsmentioning
confidence: 53%
“…There are many vital structures in this area, which contains the parotid gland and minor salivary glands, the VII, IX, X and XI cranial nerves, the cervical sympathetic nerve, lymph nodes, the internal jugular vein, the external carotid artery and its branches, and especially, the internal carotid artery (10,11). The internal carotid artery is a terminal branch of the common carotid artery.…”
Section: Discussionmentioning
confidence: 99%